Network pharmacology-based study of the anti-oxidative mechanism of san miao wan in treatment of arthritis - Xue-Qin Hao; Yan-Qi Kou; Xiao-Juan Xie; Jiao-Wang; Jing-Bo Lv; Jie Su; Ke-Xin Liu; Gao-Feng Liang (World Journal of Traditional Chinese Medicine, 2022)
San Miao Wan (SMW) is a traditional Chinese medicine (composed of Cortex phellodendri, Rhizoma atractylodes, and Radix cyathulae) widely used in China to treat arthritis; however, its underlying mechanism remains unknown. We established the target gene library of SMW and performed gene ontology enrichment analysis of related target genes. The component-target protein-protein interaction (PPI) network of SMW and the disease-target PPI network of arthritis were merged to form a core PPI network. Finally, the anti-oxidative effect of SMW for treating arthritis was evaluated in a rat arthritis model induced by sodium urate. The results showed that R. atractylodes contained four active components with 68 target proteins, R. cyathulae contained two active components and 139 target proteins, and C. phellodendri contained eight active components and 275 target proteins. The target genes of R. cyathulae were highly related to the synthesis and metabolism of reactive oxygen species, while target genes of R. atractylodes and C. phellodendri were highly related to the circulatory system. The component-target PPI network of SMW and the disease-target PPI network of arthritis predominantly overlapped. In vivo, SMW effectively reduced knee swelling induced by sodium urate, decreased serum malondialdehyde levels, and increased serum superoxide dismutase levels. In conclusion, the therapeutic effects of SMW in arthritis are associated with its anti-oxidative properties.